P089 Secukinumab Induced Ulcerative Colitis in a Patient With Psoriatic Arthritis: A Novel Approach to Refractory Cases. (December 2019) - Sethi, Vikas; Jacobs, Adam; Sethi, Ashwani
Abstract : INTRODUCTION: Secukinumab is an anti-IL 17A monoclonal antibody currently used to treat psoriasis, ankylosing spondylitis, and psoriatic arthritis. It may induce inflammation in the GI tract causing exacerbation of IBD and rarely causing IBD de novo. This phenomenon itself is seldom documented with only a handful of case reports in the US and overseas. The few cases of psoriatic arthritis and Secukinumab- induced UC were managed successfully with infliximab. However, there have been no case reports managing patients refractory to TNF-alpha inhibitors. This case illustrates an alternative therapy for management of Secukinumab- induced UC who have previously failed anti-TNF treatment for psoriatic arthritis. CASE DESCRIPTION: A 52-year-old female with a past history of psoriatic arthritis on Secukinumab presented with one-month history of bloody diarrhea. Colonoscopy showed diffuse ulcerative colitis (UC) from hepatic flexure to rectum. Biopsies showed crypt abscesses consistent with inflammatory bowel disease (IBD) along with a positive serum p-ANCA. The patient had no prior history of ulcerative colitis with a negative screening colonoscopy 2 years ago. Stool studies were negative for infection and biopsies were negative for CMV colitis. CT Scan of Abdomen and Pelvis showed no small intestinal disease. This patient had failed prior treatment for her psoriatic arthritis with Etanercept, Leflunomide, Adalimumab and Methotrexate. Secukinumab was discontinued and the patient was started on prednisone 40 mg po daily along with mesalamine 4.8 gm po daily. She improved and was discharged home. Later, she was started on Tofacitinib 10mg po bid to treat both psoriatic arthritis and ulcerative colitis to allow prednisone taper. The patient continued to improve with resolution of the bloody diarrhea along with symptomatic and objective improvement of her psoriatic arthritis. DISCUSSION: There have been case reports of Ulcerative Colitis developing in patients being treated with Secukinumab for psoriatic arthritis and Ankylosing Spondylitis. During phase three clinical trials of Secukinumab, only two patients, 0.058% of the subject population, on Secukinumab developed new onset IBD. In case reports of Secukinumab induced- UC, patients were successfully treated with the monoclonal TNF-alpha antibody, infliximab. However, in this case, the patient had already failed prior therapy with a monoclonal TNF-alpha antibody, Adalimumab, and a soluble TNF decoy receptor, Etanercept. Given her resistance to multiple forms of TNF-alpha inhibition, she was started on Tofacitinib, an inhibitor of JAK1 and JAK2 kinase, approved for both psoriatic arthritis and ulcerative colitis. There are no documented case reports treating both these conditions that are refractory to other biologics. In this subset of rare patients, this case illustrates a novel approach of using Tofacitinib in achieving therapeutic response for both psoriatic arthritis and ulcerative colitis.